Clima organizacional e qualidade em serviços: estudo de caso em laboratório de análises clínicas - Forno, Nara Lucia Frasson Dal (2005)
This dissertation analyses the motivation and considers aspects of organizational climate as factors that interfere in the process of production of the workers at the Clinical Analyses Laboratory (LAC) of the University Hospital of Santa Maria (HUSM). The internal environment aimed at the area of services, which appears at the beginning as a possibility for personal and professional growth of the ones involved in its performance at the same time it generates the possibility of internal conflicts with the consequent loss of quality and damages to the Institution. The main objective of this project is to contribute with information that can be actually useful being able to trigger actions of improvement concerning clinical laboratories. The methodology foresees the use of the Organizational Climate Research technique, where the variables that appeared to be relevant for the description of this case study were analysed. The results found allow to conclude that the workers of the LAC perceive their internal climate in different ways, and that the feeling of professional achievement, the personal satisfaction and the declared wish of improving the environment in the very department it is compound of, showing themselves as indicative of a positive Organizational climate. However, some negative aspects became evident, giving special attention to the impossibility of professional growth, the lack of recognition for the job performed and the Laboratory premises. Programs for the improvement of the quality in the ambit of the Laboratory require a new relationship between the organization and the internal client, one that favors the adequate consideration to their needs in order to motivate them so that they can offer the outstanding service required by the external client.